Assessing the prognostic value of respiratory oscillometry in patients with difficult-to-treat asthma - Yi-Luen Shen; Yi-An Hsieh; Yu-Ming Huang; Yi-Hao Peng; Ling-I Chen; Fang-Chuan Dai; Yu-Sheng Lin; Chien-Wen Huang (Scientific Reports, 2023)
Abstract Respiratory oscillometry is widely explored in asthma management; however, there is currently no consensus on its routine work-up in patients with difficult-to-treat asthma. We conducted a retrospective, cross-sectional study involving patients with difficult-to-treat asthma at Asia University Hospital between January 2017 and October 2020. We aimed to correlate clinical significance of respiratory oscillometry and asthma treatment outcomes including symptoms control and exacerbation in patients with difficult-to-treat asthma. Among the 69 patients enrolled in the study, a total of 26.1% of the patients experienced at least one severe or two moderate exacerbations. Patients with ACT < 20 presented a higher prevalence of higher frequency-dependent resistance (FDR; the difference in resistance at 5 Hz and 20 Hz) and frequency of resonance (Fres) than those with ACT ≥ 20. In the multivariable analysis, comorbidities, COPD or allergic rhinitis, and FDR were independent factors in increasing the odds ratio in poorly controlled asthma. (FDR ≥ 0.10 vs. < 0.10, adjusted ORR = 5.05, P = 0.037) There was a higher proportion of frequent exacerbations in patients with higher FDR (FDR ≥ 0.10 vs. < 0.10 = 30.0%:20.7%), but IOS parameters failed to predict frequent exacerbations on further analysis. FDR may be a potential clinical parameter for predicting symptom control in patients with difficult-to-treat asthma.